Aradıınız kişi (şu anda) ulaşılamıyor! The Turkish vowel system, (the so-called) ’Yumuşak g’ (ğ), and Turkish phonology: On a missed opportunity - Royer-Artuso, Nicolas (LingBaW. Linguistics Beyond and Within, 2023)
In this paper, some core premises that are held about Turkish Phonology are put into question, both theoretically and empirically. Some modifications to the Turkish phonological inventory and to the language’s phonotactic constraints are then proposed. It is shown how modifying the phonological inventory and modifying phonotactic statements about the language gives a more realistic perspective on the empirical data. In the conclusion, some new avenues of research are finally proposed.